EFEKTIVITAS KERJA PEGAWAI TERHADAP PELAYANAN ADMINISTRASI PADA KANTOR KECAMATAN MUARA WAHAU KABUPATEN KUTAI TIMUR - Agus Antonius (ADMINISTRASI PUBLIK, 2018)
The purpose of this study is to know about how the effectiveness of administrative services in this case the mastery of KK, KTP, and AK in Muara Wahau District and the factors that affect the effectiveness of administration in Muara Wahau District East Kutai Regency.This research uses descriptive qualitative research method that gives description about the effectiveness of administrative services in terms of handling KK, KTP, and AK in Muara Wahau Sub-district, East Kutai Regency. Techniques of data making used are obesrvasi techniques, interviews or interviews, and media questionnaires by selecting informants who use and issue information technically and functionally.From the results of research conducted in the field of population administration and civil registration is done in accordance with existing rules and regulations that have been established by looking at some service indicators such as simplicity in the category is very safe with a temperature of 6.67%, clarity and certainty regulation of service and cost according to the categories of 88.33% and 70%, facilities and infrastructure in the category of safe and comfortable with the value of 65% and 73.33%, the disclosure of information and services in the categories easy and explode if requested with the value of 71.67% and 63, 33%, tax rate of KK, KTP, AK cost Rp 10,000 to Rp 15,000, fair equity with 60% value, punctuality in category 1- 2 days, and efficient in exact category with value 80%. And the factors that affect the service are 1) Resources apparatus, 2) facilities and infrastructure, 3) awareness of the community.